AN ANALYSIS OF STUDENTS’ PROBLEM IN LISTENING COMPREHENSION AT THIRD SEMESTER OF UIN SJECH M. DJAMIL DJAMBEK BUKITTINGGI - Devri Aldian; Syahrul; Irwandi; Absharini Kardena (STKIP Subang, 2026)
This study aim to analyze students’ problems in listening comprehension at the third semester of the English Education Department of UIN Sjech M. Djamil Djambek Bukittinggi. This research employed a qualitative exploratory design. The informants were three lecturers and eight students selected through purposive sampling based on their listening scores. The data were collected through classroom observation and semi-structured interviews, and analyzed using thematic analysis based on Hamouda’s framework. The findings showed that students experienced five major problems: listening material, linguistic features, failure to concentrate, psychological characteristics, and listener factors. Among these, listening material became the most dominant factor, particularly related to long audio duration and unfamiliar topics. Students reported losing concentration when the audio exceeded two to three minutes and encountering difficulty understanding unfamiliar topics such as historical and scientific content. In addition, limited vocabulary significantly hindered comprehension, causing students to miss key information. Psychological factors such as anxiety and lack of confidence also reduced students’ performance. These findings indicate that students’ listening difficulties were influenced by interconnected internal and external factors. Therefore, lecturers are encouraged to provide appropriate materials, improve vocabulary instruction, and create a supportive learning environment to enhance students’ listening comprehension.